Proposta de uma plataforma para pesquisa em visão robótica - Fernandes, Fernanda Silva Chianca (2007)
The project described in this paper aims at developing control software and hardware for a robotic head with stereo vision. The movement control will be done from images aquired from the robotic head itself, using computer vision techniques and focal length information from the cameras. In the future, it is intended to install the developed system on a mobile robot and navigate it in real environments using visual information only.